1993
DOI: 10.1080/03079459308418924
|View full text |Cite
|
Sign up to set email alerts
|

Proximal femoral degeneration in growing broiler fowl

Abstract: The pathologies in proximal femora of broilers with lameness attributed to disorders of the proximal femur, including so-called 'femoral head necrosis', are described. Samples were collected from a variety of flocks, farms and production systems. Ten 'normal' broilers were also examined. Birds were identified by a characteristic lameness whereby they used a wing for support during locomotion and hip flexion (i.e. whilst sitting down). The appearance of the proximal femora at post mortem was used to place 67 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 28 publications
2
52
0
1
Order By: Relevance
“…Posteriormente, com o osso desprotegido inicia-se a degeneração óssea, sendo que esta alteração pode promover maior incidência de outras patologias locomotoras, tornando-se uma porta de entrada para patógenos (vírus e bactérias). Causa grande desconforto levando à redução do bem-estar das aves (Thorp et al, 1993), afetando-as de forma uni ou bilateralmente (Kealy, 1987).…”
Section: Introductionunclassified
“…Posteriormente, com o osso desprotegido inicia-se a degeneração óssea, sendo que esta alteração pode promover maior incidência de outras patologias locomotoras, tornando-se uma porta de entrada para patógenos (vírus e bactérias). Causa grande desconforto levando à redução do bem-estar das aves (Thorp et al, 1993), afetando-as de forma uni ou bilateralmente (Kealy, 1987).…”
Section: Introductionunclassified
“…Studies on commercial broilers in Canada showed that deformations of long bones were the primary causes of lameness, while arthritis and osteomyelitis were only associated with 10% of lameness-related losses during the last week before slaughter (Riddell and Springer, 1985). A decade earlier, a study by Thorp et al (1993) in the UK, which planned for possible cases of birds with thigh lesions, showed a high prevalence of BCO. Also, osteomyelitis was usually diagnosed in birds with lameness, studied by Thorp and Waddington (1997).…”
Section: Femoral Head Necrosismentioning
confidence: 99%
“…The etiological agent was determined to be Staphylococcus aureus. The condition, named at that time bacterial chondronecrosis with osteomyelitis (BCO), was consequently reported in broilers from various parts of the world: Australia, USA, Canada, and Europe (Griffits et al, 1984;Riddell and Springer 1985;Thorp et al, 1993;Thorp and Waddington, 1997;McNamee et al, 1998). Studies on commercial broilers in Canada showed that deformations of long bones were the primary causes of lameness, while arthritis and osteomyelitis were only associated with 10% of lameness-related losses during the last week before slaughter (Riddell and Springer, 1985).…”
Section: Femoral Head Necrosismentioning
confidence: 99%
See 2 more Smart Citations